Dynastie Europy : praca zbiorowa - Maczak, Antoni (Wroclaw : Zaklad Narodowy im. Ossolinskich Wydawn., 1997)
A short history of the major royal houses of Europe.
Includes bibliographical references and index.
Keywords: Europe -- Kings and rulers